PENGARUH KOMPENSASI DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI NON PNS PADA DIREKTORAT JENDERAL PENDIDIKAN SEKOLAH MENENGAH ATAS KEMENTRIAN PENDIDIKAN BUDAYA RISET DAN TEKNOLOGI JAKARTA SELATAN - Na’imah; Nariah (Journal of Research and Publication Innovation, 2024)
This research aims to analyze the influence of compensation and work motivation on the performance of non-PNS employees at the Directorate of "Senior High School" Development, Directorate General of Basic Education, Ministry of Research, Technology and Higher Education Indonesia, South Jakarta. The total sampling method was used to obtain 73 samples. Multiple linear regression analysis assisted by SPSS 26 was used in this research. The results show that work compensation and work motivation have a partial and simultaneous positive effect on performance. Linear regression equation for work compensation on performance Y = 21,282 + 0,374X1 the calculated t value is 2,905> t table 1,666, the correlation value is 0,501 and the coefficient of determination is 0,240. Linear regression equation for work motivation on performance Y = 20,723 + 0,336 X2 the calculated t value is 2,619> t table 1,666, the correlation value is 0,485 and the coefficient of determination is 0,224. Work compensation and work motivation also have a fairly strong positive relationship with performance. These results show that if compensation and motivation are increased, employee performance will also increase. The multiple linear regression equation Y = 15,092 + 0,253X1 + 0,211X2,  the calculated F value is 16,284, the correlation value is 0,563 and the coefficient of determination is 0,298.